2017
DOI: 10.1016/j.ijsu.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Is laparoscopic appendectomy feasible for complicated appendicitis ?A systematic review and meta-analysis

Abstract: LA was feasible and safe for complicated appendicitis, and it not only could shorten the hospital stays and the time until oral intake, but it could also reduce the risk of surgical site infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 45 publications
4
63
1
2
Order By: Relevance
“…Regarding cost-effectiveness, intra-abdominal abscess is an especially serious complication and a reported primary drawback of laparoscopic appendectomy. [37] Some authors reported that insu ation and irrigation during laparoscopic appendectomy for complicated appendicitis may increase the incidence of intra-abdominal abscess. [38] [39] This complication leads to a prolonged hospital stay, possible readmission, and the need for subsequent treatment, which increases costs and decreases utility of laparoscopic appendectomy in patients with complicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cost-effectiveness, intra-abdominal abscess is an especially serious complication and a reported primary drawback of laparoscopic appendectomy. [37] Some authors reported that insu ation and irrigation during laparoscopic appendectomy for complicated appendicitis may increase the incidence of intra-abdominal abscess. [38] [39] This complication leads to a prolonged hospital stay, possible readmission, and the need for subsequent treatment, which increases costs and decreases utility of laparoscopic appendectomy in patients with complicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al showed laparoscopic appendectomy has more benefit of short length of hospital stays, faster recovery time for oral intake ,and lower rate of surgical site infection than open appendectomy. 3 Wang et al also presented laparoscopic technique is feasible, safe, and efficacious for children with complicated appendicitis. 6 Yeh represented hospital mortality and readmission rates for postoperative complications did not differ between laparoscopic appendectomy and open appendectomy in case of patients with comorbidities, the elderly with complicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…With advances and improvements of laparoscopic instruments and surgeon's technique, CLA has been also applied for treatment of complicated appendicitis such as gangrenous, perforated appendicitis, or periappendiceal abscess. 3 Minimally invasive appendectomy techniques thereafter have been developed, and Single Incision Laparoscopic Appendectomy (SILA) was introduced in 2003. Despite of technical and ergonomic difficulty, SILA has become one of the most popular procedure among the single incision laparoscopic surgery with safety and feasibility in terms of complications, post-operative pain and recovery and better cosmetic results.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic surgery for uncomplicated appendicitis has been rapidly accepted, as it has several advantages over open surgery . It has also been shown to be feasible and safe for complicated appendicitis, with the advantage of a reduced risk of surgical site infection . Single‐site laparoscopic surgery has developed in recent years due to minimized surgical trauma.…”
Section: Introductionmentioning
confidence: 99%